Analisis Strategi Pengelolaan Keuangan Mesjid Dalam Meningkatkan Kepercayaan Donatur Mesjid Al-Markaz Al-Ma’arif Kab. Bone - Asmaul Husna; Ahmad Abdul Mutalib; Abd Rasyid R (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This research aims to analyze the financial management strategies of the Al-Markaz Al-Ma'arif Mosque in Bone Regency in enhancing donor trust. With the significant growth of mosques and the Muslim community in Indonesia, financial management of mosques has become crucial to ensure transparency, accountability, and efficiency in the use of funds. This study employs a qualitative method with a field approach, involving interviews and observations of mosque administrators and donors. The findings indicate that the financial management of the mosque is carried out through several funding sources, including donation boxes, voluntary contributions (infak), and productive businesses managed by the mosque administrators. The strategies implemented include managing finances based on the principles of trust, transparency in financial reporting, accountability in fund usage, efficiency and effectiveness, fairness, and compliance with Sharia law. This research finds that donor trust can be enhanced through good management and effective communication between administrators and donors. Additionally, challenges faced in financial management, such as a lack of understanding of accounting among administrators, were also identified. Therefore, this study recommends strategic steps to improve the financial management of the mosque to better empower the community and increase donor trust.